Black Phosphorene Modified Electrochemical Sensor for Fast Determination of 5‐Hydroxymethyl‐2‐furfural in Milk. Issue 12 (13th September 2021) - Li, Yuzhen; Huang, Lu; Weng, Xuexiang; Liu, Zhenmin; You, Chunping
Abstract: The fast detection of 5‐hydroxymethyl‐2‐furfural (HMF) in food industry is vital because of its toxicity and mutagenicity. A glassy carbon electrode (GCE) modified with black phosphorene (BP) nanosheets was prepared and coated with Nafion to improve stability. The electrode has excellent electrochemical stability and current response for HMF electroreduction. The good linear relationship is in the concentration range of 0.1–10 μg/mL with the detection limit of 0.012 μg/mL. HMF electroreduction is a diffusion‐controlled process involving two electrons and two protons. The sensor was successfully applied to the measurement of HMF in milk with the recovery values of 92.92 %–96.33 %. Abstract :